Epistemology Of Islamic Education Thought According To Mohammed Abed Al-Jabri - Iqbal, Muhammad; Safwan, Safwan; Ali, Muhammad (Dharmas Education Journal (DE_Journal), 2023)
Going with the flow and not getting carried away, is a wise word for Mohammed Abed Al-Jabri, with the steps of modernity that he built trying to introduce his epistemological building to the western world, he is a figure who borrows a lot of old discourses and polishes them in a new style so that the originals impress as it was built until now still resonates as a discourse. Thus, the purpose of this study is to ascertain Mohammed Abed Al-Jabri's interpretation of the epistemology of philosophy in Islamic education. This is because the dominant way of thinking in the Islamic world does not take into account many aspects of progress in the West or in Europe. Therefore, when someone presents a belief or concept based on a philosophy, it arouses suspicion. This research includes qualitative literature research, which involves collecting data and information using various library materials. According to the epistemology of Islamic thought, Mohammed Abed Al-Jabri, which is based on the approaches of Bayani, Irfani, and Burhani, the epistemology of Islamic education aspires to produce and acquire knowledge.